IMPROVING SOLUBILITY OF METHOTREXATE BY SOLID DISPERSION - MOHAMAD ALI ALALI, MUQDAM MAHDI; AL-MOUSAWY, JINAN M.; KADHIM, ZAHRAA MOHAMMED; ASHOOR, JAMAL ALI (International Journal of Applied Pharmaceutics, 2023)
Objective: Methotrexate (MTX) is a folate antimetabolite used for the management of neoplastic diseases like leukemia and breast cancer, Methotrexate is also used in the treatment of psoriasis as well as rheumatoid arthritis. The goal of this research was to improving the solubility and dissolution profile of methotrexate solid dispersion by using different polymers. Methods: A total six formulas were prepared as solid dispersion of methotrexate by solvent evaporation method by using polyethylene glycol (PEG-4000) and poly Vinyl pyrolidone (PVP-K30) as polymeric solubilizer in ratio (1:1,1:2,1:4), Then the solid dispersion of methotrexate were evaluated by solubility test, permeability test and FTIR study. Results: All six solid dispersion formulas showed a significant improvement in the solubility of methotrexate, and the formulations demonstrated improved in the rate of drug release of approximately 99.8±0.9 within 60 min. FTIR study for F3 and F6 show no drug-excipients interaction. Conclusion: Methotrexate was successfully enhanced its water solubility by using solid dispersion.